2020
DOI: 10.1186/s13613-020-0635-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher glycemic variability within the first day of ICU admission is associated with increased 30-day mortality in ICU patients with sepsis

Abstract: Background: High glycemic variability (GV) is common in critically ill patients; however, the prevalence and mortality association with early GV in patients with sepsis remains unclear.Methods: This retrospective cohort study was conducted in a medical intensive care unit (ICU) in central Taiwan. Patients in the ICU with sepsis between January 2014 and December 2015 were included for analysis. All of these patients received protocol-based management, including blood sugar monitoring every 2 h for the first 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 29 publications
7
53
0
2
Order By: Relevance
“…Glucose variability during the hospitalization may amplify these phenomena (53), worsening the prognosis. Also deserving attention is the fact that high glycemic variability is predictive per se of high ICU mortality (54). Therefore, it has already been suggested that the management of glucose variability has to be part of the more comprehensive approach to the management of hyperglycemia today: it seems that this must be urgently applied in ICUs (53).…”
Section: Management Of Hyperglycemia and CV Risk In People With Diabementioning
confidence: 99%
“…Glucose variability during the hospitalization may amplify these phenomena (53), worsening the prognosis. Also deserving attention is the fact that high glycemic variability is predictive per se of high ICU mortality (54). Therefore, it has already been suggested that the management of glucose variability has to be part of the more comprehensive approach to the management of hyperglycemia today: it seems that this must be urgently applied in ICUs (53).…”
Section: Management Of Hyperglycemia and CV Risk In People With Diabementioning
confidence: 99%
“…The main goals of in-hospital glucose monitoring are to limit abnormal glycemic variability (time in range >70%) and minimize hypoglycemic episodes (time in hypoglycemia <4%) [ 103 ]. Increased glycemic variability, defined as fluctuations between abnormally high and low glucose levels [ 104 ], has been recognized as an important adverse prognostic factor for critically ill patients, especially in the ICU setting [ 105 ]. Hypoglycemia can be also detrimental for severely infected patients, since it stimulates the release of stress hormones, such as cortisol and catecholamines, leading to elevated levels of circulating inflammatory mediators and the augmentation of pre-existing inflammation [ 106 ], and may also exert arrhythmogenic effects by prolonging the QT interval, thus increasing cardiovascular mortality [ 94 ].…”
Section: General Recommendations For the Management Of Hyperglycemmentioning
confidence: 99%
“…Finally, there are plenty of reports in the literature that glucose variability is producing a worsening of the prognosis in ICU [ 16 , 19 22 ] even when glucose is kept in normal range [ 22 ]. So it seems advisable that glucose variability should be avoided.…”
Section: Glycemic Controlmentioning
confidence: 99%
“…In the pandemic "Corona Virus Disease 2019" (COVID- 19) people with diabetes have a high risk to require ICU admission. The management of diabetes in Intensive Care Unit is always challenging, however, when diabetes is present in COVID-19 the situation seems even more complicated.…”
Section: Introductionmentioning
confidence: 99%